Recycling of municipal waste in Slovak cities - Skamlova, Lucia; Klobučník, Michal (Bulletin of Geography. Socio-economic Series, 2021)
Among the most urgent topics within waste management policy is the gradual transition of the economy from a linear model towards a circular economy with a more sustainable way of using resources. The European Union has responded to these changes by passing new legislation and ambitious targets so that all member states can quickly work towards achieving a greener and more sustainable Europe. However, the starting position for achieving the desired goals differs significantly from one country to another. In this paper, we therefore looked at the position of Slovakia in relation to selected waste management indicators, and at the measures taken so far. Moreover, since waste management falls under one of the many public benefit services provided under the remit of local governments, we also monitored the specific contribution of Slovak cities to the newly established trend of waste management in the country.